2016
DOI: 10.1111/1095-9270.12179
|View full text |Cite
|
Sign up to set email alerts
|

Recording and Analysis of Ship Graffiti in St Thomas’ Church and Blackfriars Barn Undercroft in Winchelsea, East Sussex, UK

Abstract: Two assemblages of ship graffiti were recorded using Reflectance Transformation Imaging in the ancient port town of Winchelsea. The engravings show characteristics common to most medieval ship graffiti in England, while displaying different levels of detail, which encouraged a nuanced interpretation. It is suggested that the ship graffiti demonstrate a multifaceted relationship with the sea. The St Thomas’ church graffiti could have been a means of spiritual protection and a devotional practice that cuts acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(44 reference statements)
0
5
0
1
Order By: Relevance
“…While clothing may be useful to try and date a drawing, Gilchrist observes that in art sometimes older styles of clothing will appear in drawings rather than contemporary ones, which makes clothing less precise as a dating method, and this issue is repeated with regards to ship graffiti. However, if the inscription is written, writing styles may help discern when an inscription was made if a date is not provided (Champion 2015; Dhoop et al 2016;Gilchrist 2018;Jones-Baker 1993). Previously, Pritchard thought that most graffiti seemed to date from the twelfth century to the sixteenth; however, more recent work has shown that most graffiti, at least in the Risbridge Hundred of East Anglia, is from the early modern period based on the letter forms that are present (Alexander n.d.;Hollis 2024;Pritchard 1967).…”
Section: Recording Methods Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…While clothing may be useful to try and date a drawing, Gilchrist observes that in art sometimes older styles of clothing will appear in drawings rather than contemporary ones, which makes clothing less precise as a dating method, and this issue is repeated with regards to ship graffiti. However, if the inscription is written, writing styles may help discern when an inscription was made if a date is not provided (Champion 2015; Dhoop et al 2016;Gilchrist 2018;Jones-Baker 1993). Previously, Pritchard thought that most graffiti seemed to date from the twelfth century to the sixteenth; however, more recent work has shown that most graffiti, at least in the Risbridge Hundred of East Anglia, is from the early modern period based on the letter forms that are present (Alexander n.d.;Hollis 2024;Pritchard 1967).…”
Section: Recording Methods Of This Studymentioning
confidence: 99%
“…More recently, Matthew Champion's 2015 book Medieval Graffiti: The Lost Voices of England's Churches focuses on graffiti throughout England and their various interpretations. Many articles have also been written about graffiti in churches, though these often focus on one aspect or type of graffiti, such as ships or designs considered to have an apotropaic function (Brady and Corlett 2004;Dhoop et al 2016;Heslop et al 2013;Jones-Baker 1993;Plesch 2002). This paper will attempt to start to address a gap as it focuses on two inscriptions that mimic the style of formal artworks and place them within the historical context of the geographic region in where they are found.…”
Section: English Parish Churches and Graffitimentioning
confidence: 99%
“…In (Dhoop et al, 2016), ship graffiti were recorded using RTI in the medieval church of St. Thomas in Winchelsea (UK). Eleven possible objects were identified and recorded, including a variety of ship types.…”
Section: Related Workmentioning
confidence: 99%
“…The differences between the two drawings ( Fig. 2b, c) led the team to the decision to revisit the monument and document the graffiti with the application of Reflectance Transformation Imaging photography (RTI) (Malzbender et al, 2001; for a similar application with graffiti see Dhoop et al, 2016) ( Fig. 2a).…”
Section: The Lines That Define the Sgmentioning
confidence: 99%